Proposing a new hierarchical framework for the evaluation of quality management practices: a new combined fuzzy hybrid MCDM approach - Mardani, Abbas; Jusoh, Ahmad; Zavadskas, Edmundas Kazimieras; Zakuan, Norhayati; Valipour, Alireza; Kazemilari, Mansooreh (Journal of Business Economics and Management, 2016)
This study aims to evaluate the quality management (QM) practices in Iranian hotels that are small and medium enterprises (SMEs) through the integration of the fuzzy set theory with both qualitative and quantitative methods. The criteria were collected through the literature survey and the fuzzy Delphi method (FDM). This study applied fuzzy multiple criteria decision making (FMCDM), including the fuzzy analytic hierarchy process (FAHP), the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR). In the FDM phase, 21 practice was selected and categorized into four main factors. Results of the study indicated that the quality assurance was ranked as the highest important fac- tor. From the practical viewpoint, this paper proposed new integrated model that applied FDM, FAHP, TOPSIS and VIKOR for the evaluation of QM practices in the hotel industry and introduced the environmental perspective as a new viewpoint of QM systems, espe- cially in hotels as SMEs. In addition, the proposed model highlights a new insight into MCDM and contributes to the present body of knowledge in the area of QM systems.